DS+ : Reliable Distributed Snapshot Algorithm for Wireless Sensor Networks - Uslu, Gamze; Serdaroglu, Kemal Cagri; Baydere, Sebnem (Journal of Computer Networks and Communications (Print), 2013)
Acquiring the snapshot of a distributed system helps gathering system related global state. In wireless sensor networks (WSNs), global state shows if a node is terminated or deadlock occurs along with many other situations which prevents a WSN from fully functioning. In this paper, we present a fully distributed snapshot acquisition algorithm adapted to tree topology wireless sensor networks (WSNs). Since snapshot acquisition is through control messages sent over highly lossy wireless channels and congested nodes, we enhanced the snapshot algorithm with a sink based reliability suit to achieve robustness. We analyzed the performance of the algorithm in terms of snapshot success ratio and response time in simulation and experimental small test bed environment. The results reveal that the proposed tailor made reliability model increases snapshot acquisition performance by a factor of seven and response time by a factor of two in a 30-node network. We have also shown that the proposed algorithm outperforms its counterparts in the specified network setting.